Map Reduce Framework Driven Apriori Algorithm Base Model of Opinion Mining for drug Review (International Journal of Engineering and Computer Science, 2016)
Big data which is modern buzz word of computer science society is showing its presence in almost all the trades including medical domain. The mounting trend of blogging the opinions and feedbacks of used drug is turned to be good tool for researchers and patients to take confirmation of advantageous and disadvantageous about the consumption of drugs. The data extracted from blogs about various drugs and symptoms is a huge and turned to be a big data. So extracting use full information forma such data is a challenging task to data mining research community. Applying opinion mining concepts on map reduce frame work for drug review can lead to a useful platform to extract and answer needs of research community. We propose a map reduce framework driven apriori base model form retrieving information about various drugs and symptoms. The proposed work is extension to our previous work [1] on opinion mining of drug reviews.  The proposed model is tested on WebMD blog reviews which shown the good results.